Neural versus pneumatic control of pressure support in patients with chronic obstructive pulmonary diseases at different levels of positive end expiratory pressure: a physiological study - Liu, Ling (Crit Care, 2015)
INTRODUCTION: Intrinsic positive end-expiratory pressure (PEEPi) is a “threshold” load that must be overcome to trigger conventional pneumatically-controlled pressure support (PS(P)) in chronic obstructive pulmonary disease (COPD). Application of extrinsic PEEP (PEEPe) reduces trigger delays and mechanical inspiratory efforts. Using the diaphragm electrical activity (EAdi), neurally controlled pressure support (PS(N)) could hypothetically eliminate asynchrony and reduce mechanical inspiratory effort, hence substituting the need for PEEPe. The primary objective of this study was to show that PS(N) can reduce the need for PEEPe to improve patient-ventilator interaction and to reduce both the “pre-trigger” and “total inspiratory” neural and mechanical efforts in COPD patients with PEEPi. A secondary objective was to evaluate the impact of applying PS(N) on breathing pattern. METHODS: Twelve intubated and mechanically ventilated COPD patients with PEEPi ≥ 5 cm H(2)O underwent comparisons of PS(P) and PS(N) at different levels of PEEPe (at 0 %, 40 %, 80 %, and 120 % of static PEEPi, for 12 minutes at each level on average), at matching peak airway pressure. We measured flow, airway pressure, esophageal pressure, and EAdi, and analyzed neural and mechanical efforts for triggering and total inspiration. Patient-ventilator interaction was analyzed with the NeuroSync index. RESULTS: Mean airway pressure and PEEPe were comparable for PS(P) and PS(N) at same target levels. During PS(P), the NeuroSync index was 29 % at zero PEEPe and improved to 21 % at optimal PEEPe (P < 0.05). During PS(N), the NeuroSync index was lower (<7 %, P < 0.05) regardless of PEEPe. Both pre-trigger (P < 0.05) and total inspiratory mechanical efforts (P < 0.05) were consistently higher during PS(P) compared to PS(N) at same PEEPe. The change in total mechanical efforts between PS(P) at PEEPe(0%) and PS(N) at PEEPe(0%) was not different from the change between PS(P) at PEEPe(0%) and PS(P) at PEEPe(80%). CONCLUSION: PS(N) abolishes the need for PEEPe in COPD patients, improves patient-ventilator interaction, and reduces the inspiratory mechanical effort to breathe. TRIAL REGISTRATION: Clinicaltrials.gov NCT02114567. Registered 04 November 2013.